The thing about pain: The remaking of illness narratives in chronic pain expressions on social media. (September 2016) - Gonzalez-Polledo, Elena; Tarr, Jen
In this article, we analyse chronic pain narratives on Flickr and Tumblr. We focus on how, by incorporating visual and multimodal elements, chronic pain expressions in social media significantly extend and challenge the logic, function and effects of traditional 'illness narratives'. We examine a sample of images and blogs related to chronic pain and formulate a typology of chronic pain expressions on these sites. Flickr brings a form of narrative immediacy, making the pain experience visible, eliciting empathy and marking chronicity. Tumblr lends itself to more networked forms of interaction through the circulation of multimodal memes, and support communities are built through humour and social criticism. We argue that new forms of mediation and social media dynamics transform pain narratives. This has implications for our understandings of the forms and formats of pain communication and offers new possibilities for communicating pain within and beyond clinical contexts.